Rekonstruksi Paradigma Pendidikan Islam Dalam Menghadapi Pluralisme Sosial Dan Krisis Nilai Keagamaan Kontemporer: Reconstructing Islamic Education Paradigms to Address Social Pluralism and Contemporary Religious Value Crises - Imam Anas Hadi; MHD. Sandi Azhar; Gan Gan Nurbanani (Educan, 2026)
This study highlights the need to reconstruct the paradigm of Islamic education to address social diversity and the growing crisis of religious belief in the modern world. Islamic education is still dominated by a normative paradigm that focuses on textual teaching, thereby reducing its responsiveness to social dynamics and changes in the expression of Islam. The purpose of this study is to analyze this paradigm and provide a conceptual framework for Islamic education that is more relevant to a pluralistic society. This study uses a qualitative approach with a literature review method. Scientific sources include journal articles and scientific papers discussing Islamic education, social pluralism, and religious beliefs. Data analysis was conducted using content analysis to identify patterns of thought, paradigm shifts, and the relationship between Islamic education and contemporary social realities. The results of this study indicate that the normative paradigm of Islamic education tends to support the role of religious education as a means of establishing social and ethical norms. Social pluralism and the crisis of Islamic faith are difficult to understand as threats, but rather as realities that influence the direction, purpose, and function of Islamic education. This study highlights the importance of an inclusive, contextual, and reflective paradigm in Islamic education, using education as a forum for discussion between Islamic teachings and social realities. With this paradigm shift, it is hoped that Islamic education can strengthen its ability to develop moderate, adaptive, and relevant religious practices in a pluralistic society.